Critical Analysis of Indonesia’s Cybersecuritization Discourse: Deconstructing the Identification of Securitizing Actors - Kamil Ghiffary A; Hartanto Hartanto; Ivandra Solihin (Journal of Business, Social and Technology, 2026)
Background: The discussion regarding Securitization Theory in academic literature about state reactions to digital threats is growing alongside the development of Indonesia's digital threat landscape. Yet, this study highlights a methodological shortcoming: existing literature often derives from overly simplistic theories, treating securitization as a mere contextual phenomenon rather than assuming it as an active constructivist frame. Objective: By juxtaposing the structural grammar of the Copenhagen School theory with Myriam Dunn Cavelty’s concept of cybersecuritization, this paper critically engages with recent literature on Indonesia’s cybersecuritization. Methods: Using a qualitative-descriptive Critical Literature Review, this study employs the existing academic discourse as its primary data source, addressing the need to deconstruct two fundamental theoretical building blocks of the concept of securitization—securitizing actors and speech acts. Results: The findings indicate that previous research misapplied the concept of the speech act, taking routine political (locutionary) rhetoric literally and failing to deconstruct its illocutionary intent, contextual purpose, or sequentiality. Moreover, the literature remains grounded in traditional, realist models of "existential threats" and tends to overlook technocratic, risk-management practices and non-traditional actors that characterize modern cybersecurity governance. In conclusion, this study advocates for a methodological recommitment, recommending that researchers combine language-specific indicators with features unique to the digital environment. Conclusion: Acknowledging its focused scope on actors and speech acts, this paper recommends that future research explore the remaining components of the cybersecuritization framework to achieve a complete and dynamic understanding of Indonesia's digital security institutionalization.